Autonomy of lower-level perception from global processing in autism: Evidence from brain activation and functional connectivity - Liu, Yanni (Neuropsychologia, 2011)
Previous behavioral studies have shown that individuals with autism are less hindered by interference from global processing during the performance of lower-level perceptual tasks, such as finding embedded figures. The primary goal of this study was to examine the brain manifestation of such atypicality in high-functioning autism using fMRI. Fifteen participants with high-functioning autism and fifteen age-and IQ-matched typical controls were asked to perform a lower-level perceptual line-counting task in the presence of a distracting depiction of a 3-D object, in which participants counted whether there were more red or more green contours (In a contrasting 3-D task, participants judged whether the same 3-D stimulus objects (but without color in any contours) depicted a possible or impossible 3-D object). We hypothesized that individuals with autism would be less likely than controls to process the global 3-D information (and would hence show fewer neural signs of such interfering 3-D processing) during the lower-level line-counting task. The fMRI results revealed that in the line-counting task, the autism group did not show the increased medial frontal activity (relative to the possibility task), or the increased functional connectivity between the medial frontal region and posterior visual–spatial regions, demonstrated by the control group. Both findings are indices of lesser effort and difficulty in the line-counting task for the autism group than for the control group, attributed to less interference from the 3-D processing in the autism group. In addition, in the line-counting task, the control group showed a positive correlation between a measure of spatial ability (Vandenberg scores) and activation in the medial frontal region, suggesting that more spatially able control participants did more suppression of the irrelevant 3-D background information in order to focus on the line-counting task. The findings collectively indicate that the global 3-D structure of the figure had a smaller effect, if any, on local processing in the group with autism compared to the control group. The results from this study provide the first direct neural evidence of reduced global-to-local interference in autism.